Environmental factors and microbial interactions drive microbial community succession during solid-state fermentation of corn husk for microbial biomass protein production - Yan, Yaping; Sun, Yinan; Cui, Jinna; Gao, Junjie; Chai, Yingnan; Liu, Zhanying (Frontiers in Microbiology, 2025)
Corn husk, a predominant byproduct derived from intensive corn processing, is characterized by high cellulose content, low protein content, and poor palatability, which makes it difficult to be fully utilized by ruminants. This investigation employed corn husk as substrate for microbial protein production through a two-stage open solid-state fermentation (SSF) system using Aspergillus niger and yeast strains. The fermentation process yielded a 65.12% enhancement in true protein content. Analysis of microbial community succession dynamics and their regulatory determinants revealed critical correlations with microbial protein production efficiency. Random forest analysis combined with co-occurrence network modeling revealed distinct microbial community dynamics across fermentation phases. During the initial phase (P1), Bacillus and Aspergillus dominated the community, with their core modules significantly influenced by capillary water, free water, and pH. In the later phase (P2), Saccharomyces and Cyberlindnera took over as dominant genera, primarily shaped by capillary and free water. The constructed microbial consortium comprising Aspergillus, Saccharomyces, and Cyberlindnera exhibited multifactorial regulation involving temperature, pH, capillary water, and free water, along with complex interspecies interactions with members of Firmicutes and Proteobacteria. These findings provide valuable guidance for targeted manipulation of microbial community succession during corn husk fermentation and optimization strategies for microbial biomass protein.